THE INTERNALIZATION OF SPIRITUAL BASED CHARACTERS VALUE IN BUILDING THE CULTURE OF EDUCATION ORGANIZATION - J Juharyanto (International Research-Based Education Journal, 2017)
This study describes characters' value integration in developing an organizational culture in education which has got various significance changes in all aspect. This obviously can be seen from the lecturers' professionalism programs, students' output as well as the ongoing physical development. This is a qualitative research involving a case study design. The data was collected through observation, documentation, and deep interview techniques, and then analyzed through (1) data reduction, (2) data presentation, and (3) conclusion. From data analyzed, shows that the integration of characters based on Islamic values in constructing organization culture in STAI shows more effective impact. The values involve (1) love, (2) sincerity, (3) patient, (4) professional activities, (5) God's Blessing, and (6) The awareness of previous histories. Keywords: spiritual based characters values; organizational culture